BUMDES DI KECAMATAN KABAWETAN : KAJIAN MANFAAT BAGI MASYARAKAT - Indah Permata Sari; Retno A. Ekaputri (Convergence: The Journal of Economic Development, 2019)
The purpose of this study was to determine the condition of BUMDes in Kabawetan district, Kepahiang Regency. The analytical method used is descriptive qualitative analysis. The data used in this research is secondary data. The results of this study indicate that the condition of BUMDes has gone well, BUMDes have been equipped with village regulations and village head decisions with adequate capital participation. Then BUMDes has a complete management and has several types of businesses. Keywords : BUMDes , Rural Economic